Hyperbaric Oxygen Promotes Chronic Wound Healing in Sprague-Dawley Rats by Inhibiting Pyroptosis - Ma, H; Wei, X; Lin, E; Wang, Y; Huang, J; Wei, H (Physiological research, 2024)
This study aimed to establish a rat model of chronic wounds to observe the effects of hyperbaric oxygen (HBO) on chronic wound repair and pyroptosis and explore the potential role of pyroptosis in the pathogenesis of chronic wounds. Sprague-Dawley (SD) rats were randomly divided into acute wound group (control group), chronic wound group (model group), chronic wound + HBO treatment group (HBO group), and chronic wound + VX-765 (IL-converting enzyme/Caspase-1 inhibitor) treatment group (VX-765 group). After 7 days of respective interventions, the wound healing status was observed, and wound tissue specimens were collected. Hematoxylin and eosin (HE) staining was used to observe the pathological changes in wound tissues. Transmission electron microscopy was used to observe the changes in cellular ultrastructure. Immunofluorescence was used to observe the expression and localization of vascular endothelial growth factor A (VEGF-A) and the N-terminal domain of gasdermin D (GSDMD-N). Western blot was conducted to detect the expression of nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3), cysteine-requiring aspartate protease-1 (Caspase-1), VEGF-A, and GSDMD-N proteins in wound tissues. Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to detect the expression of NLRP3, Caspase-1, and GSDMD genes. Enzyme-linked immunosorbent assay (ELISA) was performed to observe the expression of the inflammatory cytokines interleukin-1 beta (IL-1beta) and IL-18. The results showed that the HBO group had a faster wound healing rate and better pathology improvement compared to the model group. The expression level of VEGF-A was higher in the HBO group compared to the model group, while the expression levels of NLRP3, Caspase-1, GSDMD, IL-1beta, and IL-18 were lower than those in the model group. HBO can effectively promote the healing of chronic wounds, and the regulation of pyroptosis may be one of its mechanisms of action. Keywords: Hyperbaric oxygen, Pyroptosis, Chronic wounds, Inflammatory.
Keywords: Wound Healing; Rats; protein NLRP3; vaskulární endoteliální růstový faktor A; potkani Sprague-Dawley; Chronic Disease; chronická nemoc; mužské pohlaví; Gasdermins; Hyperbaric Oxygenation; Phosphate-Binding Proteins; hojení ran; Pyroptosis; krysa rodu Rattus; hyperbarická oxygenace; zvířata; proteiny vázající fosfáty; gasderminy; NLR Family, Pyrin Domain-Containing 3 Protein; Vascular Endothelial Growth Factor A; Rats, Sprague-Dawley; pyroptóza; Male; Animals